CT 영상을 이용한 3D 프린팅으로 환자 맞춤형 대퇴골 첨삭가공 - 오왕균; Wang Kyun Oh; 임기선; Ki Seon Lim; 이태수; Tea Soo Lee (Journal of the Korean Society of Radiology, 2013)
대퇴골은 사람의 뼈 중 가장 길며 체중을 지탱하는 골격체로 대퇴골간은 긴 파이프 모양이면서 안에 해면골이 거의 없어서 골절이 발생되면 재생이 어렵다. 사고로 인하여 발생되는 대퇴골의 골절은 골간부가 가장 높은 빈도로 발생한다. 골절의 수술방법은 골수강에 IM Nail을 삽입하여 골절부위를 고정하는 IM Nailing이다. 수술 시 대퇴골의 중심으로 진입하지 못하면 2차 골절 등의 피해가 발생하기도 한다. 본 연구에서는 수술 전 대퇴골의 CT IMAGE을 이용하여 3D 프린터로 환자 맞춤형 대퇴골을 제작하여 골수강으로 IM Nailing 시뮬레이션을 할 수 있도록 하였다. 수술 중발생할 수 있는 2차적 손상을 방지 하고 시간 단축, 정밀한 수술을 할 수 있을 것이다. Femur is the largest bone in the human body which supports the weight of body. A long pipeline shape of femur has little cancellous bone, so that regeneration is difficult when fracture happens. The fracture caused by an accident most frequently occurs at diaphysis. IM Nailing is the surgical method that implants an IM Nail into a medullary cavity for the fixation of fracture parts. However, a secondary fracture may happen if an IM Nail does not penetrate at the center of femur. In this study, a patient-specific femur was manufactured by a 3D printer using the computed tomography images scanned before surgery, which was used for the simulation of IM Nailing. It is expected that this result may prevent the secondary damage, reduce surgical operation time, and increase the precision.